2000
DOI: 10.1086/317522
|View full text |Cite
|
Sign up to set email alerts
|

Pyrogen Sensing and Signaling: Old Views and New Concepts

Abstract: Fever is thought to be caused by endogenous pyrogenic cytokines, which are elaborated and released into the circulation by systemic mononuclear phagocytes that are activated by exogenous inflammatory agents and transported to the preoptic-anterior hypothalamic area (POA) of the brain, where they act. Prostaglandin (PG) E2 is thought to be an essential, proximal mediator in the POA, and induced by these cytokines. It seems unlikely, however, that these factors could directly account for early production of PGE2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 75 publications
1
62
0
1
Order By: Relevance
“…PGE 2 is a well-known inductor of fever (16). In a rat model of LPS-induced fever (19), upregulation of the enzymes that me- diate its generation was shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGE 2 is a well-known inductor of fever (16). In a rat model of LPS-induced fever (19), upregulation of the enzymes that me- diate its generation was shown.…”
Section: Discussionmentioning
confidence: 99%
“…In general, fever-generating PGE 2 is thought to be produced in the brain (16). Nevertheless, it is shown that substantial amounts of peripheral PGE 2 enter hypothalamic structures (17), and recent data support the idea of blood-derived PGE 2 's playing an important role in fever (18,19).…”
mentioning
confidence: 99%
“…It relies on the stimulation of peripheral sensory nerves, i.e. vagal (Blatteis et al, 2000;Romanovsky, 2000) and trigeminal (Navarro et al, 2006) afferences by PGE 2 . The presumed pathway consists of a first synapse in the nucleus of the solitary tract (NTS), followed by travelling of the signal via ventral noradrenergic bundle to the POA where it induces the release of NE, hence stimulating synthesis of PGE 2 .…”
Section: The Neural Pathwaymentioning
confidence: 99%
“…Nonetheless, evidence exists that these molecules reach the brain by at least two mechanisms: a) systemic circulation and b) neural pathways (reviewed by Banks and Quan and Banks) [5,97]. Cytokines within systemic circulation may affect blood-brain barrier (BBB) permeability, may bind to areas of the brain that lack a BBB such as circumventricular organs [10], may cross through fenestrated capillaries of the BBB or may use cytokine-specific transporters [11]. Cytokines may also activate brain endothelial and perivascular cells [106] to induce production of other signaling molecules such as nitric oxide (NO), prostanoids or other cytokines that in turn stimulate glial cells [54,63,97].…”
Section: Inflammation and Pro-inflammatory Cytokinesmentioning
confidence: 99%